DAMPAK KEMASAN TERHADAP KUANTITAS PENJUALAN PRODUK USAHA AGROINDUSTRI CV. TULI MARIO DI TANGKIT BARU KOTA JAMBI - Nida Kemala; Siti Abir Wulandari (Universitas Batanghari Jambi, 2015)
The research was conducted inthepineapple agro-based Tangkit Baru, JambiCity could”CV. Tuli Mario”. It was held to analyze the impact of industry package onthe selling product of this agroindustry.The Chi-Square Testwas applyied as an instrument in this research.The result of the researchshowedthatthere was significantly distinguish of the numbers of the selling product on this pineapple agro-based Industry despite of the packaging become different. The average number of selling product was indicated decrease from 1.003 units go down by 731 units. It was likely caused by the preferencychanging of the costumers. In the other hand it was probability caused by high number of its subtitution products.Keyword : pineapple, agroindustry, package